2011
DOI: 10.1002/anie.201006844
|View full text |Cite
|
Sign up to set email alerts
|

Photon‐Quantitative Reaction of a Dithiazolylarylene in Solution

Abstract: In the cascade of mammalian vision, the cis-to-trans photoisomerization reaction of the retinal chromophore bound to the opsin apoprotein acts as the first trigger for the conversion of light signals into electrical pulses, which are finally transmitted to the brain. One of the specific chemical characteristics of retinal chromophore is its high quantum yield of cis-to-trans photoisomerization, F cis-trans = 65 %, which affords the high sensitivity of the rod rhodopsin, an opsin-retinal complex required for ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
161
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(169 citation statements)
references
References 27 publications
6
161
0
2
Order By: Relevance
“…[19] Because both molecules are composed of similar molecular units and display dual non-covalent intramolecular interactions, one may expect similar photochromic reactivity. Indeed, the photochromic quantum yield of 1a was similar to that of 3a in hexane (90 % for 1a and 98 % for 3a), whereas that of 3a was significantly suppressed in methanol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Because both molecules are composed of similar molecular units and display dual non-covalent intramolecular interactions, one may expect similar photochromic reactivity. Indeed, the photochromic quantum yield of 1a was similar to that of 3a in hexane (90 % for 1a and 98 % for 3a), whereas that of 3a was significantly suppressed in methanol.…”
Section: Resultsmentioning
confidence: 99%
“…The authors recently reported that a dithiazolylbenzothiophene derivative shows a photon-quantitative reaction with almost 100 % photocyclization quantum yield. [19] This extremely high photochromic reactivity of the molecule was explained in terms of specific intramolecular S/N and CH/N non-covalent interactions, which were thought to stabilize the C 2 -symmetric conformation in nonpolar solvents. In the field of supramolecular chemistry, intramolecular and inter-arylene unit interactions have been developed to regulate the rotational configuration of oligoarylene molecules forming specific foldamers.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades photochromic diarylethenes bearing azole units [28][29][30][31][32] have attracted much attention because of their potential ability to form hydrogen bond and the possibility of its application as an effective tool for the spatiotemporal control of switchable biological systems. 33 Therefore, the development of an alternative method for the preparation of diary(hetaryl)lcyclopentenes based on azoles, primarily unsymmetrical, is of most importance for the design of new smart materials for various fields of science, medicine and technology.…”
Section: Page 1 Of 5 Rsc Advancesmentioning
confidence: 99%
“…The rates of isomerization in the initial stage of the reaction (0-5%) were compared with reference whose Φ oc (35%) in hexane are known, which brought forth 5% Please do not adjust margins Please do not adjust margins uncertainties on the calculations of quantum yields. 43 Absorption changes were monitored by a CCD camera mounted on a Princeton spectrometer instrument.…”
Section: Instrumentationmentioning
confidence: 99%